2016
DOI: 10.1186/s12863-016-0339-8
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium, persistence of phase and effective population size estimates in Hereford and Braford cattle

Abstract: BackgroundThe existence of moderate to high levels of linkage disequilibrium (LD) between genetic markers and quantitative trait loci (QTL) affecting traits of interest is fundamental for the success of genome-wide association (GWAS) and genomic selection (GS) studies. Knowledge about the extent and the pattern of LD in livestock populations is essential to determine the density of single nucleotide polymorphisms (SNP) required for accurate GWAS and GS. Moreover, observed LD is related to historical effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 50 publications
8
18
1
Order By: Relevance
“…The average of r 2 varied across autosomes (ranging from 0.16 in OAR26 to 0.34 in OAR10 for the pairwise distance of < 10 kb), which is in line with previous reports in sheep (Liu et al, 2017;Prieur et al, 2017;Zhao et al, 2014), beef cattle (Bohmanova et al, 2010;Edea et al, 2015), and dairy cattle (Qanbari et al, 2010). This phenomenon can be due to variation in the recombination rate in different autosomes, natural or artificial selection, and genetic drift (Liu et al, 2017;Mastrangelo et al, 2017;Qanbari et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The average of r 2 varied across autosomes (ranging from 0.16 in OAR26 to 0.34 in OAR10 for the pairwise distance of < 10 kb), which is in line with previous reports in sheep (Liu et al, 2017;Prieur et al, 2017;Zhao et al, 2014), beef cattle (Bohmanova et al, 2010;Edea et al, 2015), and dairy cattle (Qanbari et al, 2010). This phenomenon can be due to variation in the recombination rate in different autosomes, natural or artificial selection, and genetic drift (Liu et al, 2017;Mastrangelo et al, 2017;Qanbari et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…The level of LD in Zandi sheep was less than it is in cattle (Biegelmeyer et al, 2016;Bohmanova et al, 2010;Jasielczuk et al, 2016) and pigs (Grossi et al, 2017) but close to the level of LD reported for other sheep breeds (Al-Mamun et al, 2015;García-Gámez et al, 2012;Liu et al, 2017). For example, Qanbari et al (2010) reported r 2 of 0.20±0.24 for SNPs within 50-75 kb in German Holstein dairy cattle.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It should be mentioned that the Hereford and Braford population studied here is evaluated and selected as a single breed-type with common breeding objectives and variance components by the Delta G Connection Breeding Program [24]. Moreover, as demonstrated by Biegelmeyer et al [25], correlation of marker phase between these two breeds was estimated at 0.92 for SNPs less than 50 kb apart, which further supports the assumption that the initial detection analyses based on the 50 K SNP panel was suitable [18]. Therefore, we carried out a joint analysis that accounted for breed differences and heterosis to calculate DEBV.…”
Section: Methodsmentioning
confidence: 99%
“…with the phenotypic changes. The excess of polymorphism in genome sequence data (Nez et al, 2016) has provided a valuable inventive tool in the search for traces of the most recent selection in the genome, for example, (Biegelmeyer et al, 2016).…”
mentioning
confidence: 99%